Dr. Carlos Farias Scroppo — Deep Plane Facelift — Buenos Aires - Farias Scroppo, Carlos (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Carlos Farias Scroppo, practicing in Buenos Aires, Argentina. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003085; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; argentina; buenos aires